Survey on implementation level of government services in mobile devices - Rodríguez, Rocío Andrea (2009)
When comparing Argentina’s population with the number of cellular telephony active lines, it can be assert that the active lines widely exceed the inhabitants. Because of this high concentration of cellular telephony, due to the lower cell phone’s price against computer’s price, it begins to be necessary for the government agencies to provide services that can be implemented in cellular phones. The government agencies, that opportunely, joined their efforts to provide on line services through the web, facilitating the procedures for the citizens and starting a field called eGovernment, must now consider the high insertion of the cellular phones within the population and, accordingly, facilitate the access to services from mobile devices (mServices). When mobile devices become the eGovernment communication channel, this new field of study is called mGovernment. The present paper presents the analysis of the obtained results after surveying mServices and the technology implemented by government agencies.